2021
DOI: 10.1016/j.cmi.2021.04.010
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics and factors associated with hospital admission or death in 43 103 adult outpatients with coronavirus disease 2019 managed with the Covidom telesurveillance solution: a prospective cohort study

Abstract: Objectives Studies on coronavirus disease 2019 (COVID-19) have mainly focused on hospitalized patients or those with severe disease. We aim to assess the clinical characteristics, outcomes and factors associated with hospital admission or death in adult outpatients with COVID-19. Methods This is a prospective cohort of outpatients with suspected or confirmed COVID-19, registered in Covidom telesurveillance solution for home monitoring of patients with COVID-19 in the Gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
17
1
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 29 publications
8
17
1
1
Order By: Relevance
“…[4] A cohort of 43,103 COVID-19 outpatients in France found that dyspnea was associated with an eventual requirement for hospitalization while anosmia or ageusia were associated with a decreased risk for need for hospitalization. [15] The same dyspnea and anosmia/ageusia results were found in a smaller cohort of initial outpatients in Seattle, Washington as well. [16] A meta-analysis encompassing 1813 patients revealed that dyspnea was associated with an increased risk for ICU admission (pooled OR 6.55, 95% CI: 4.28-10.0).…”
Section: Discussionsupporting
confidence: 59%
“…[4] A cohort of 43,103 COVID-19 outpatients in France found that dyspnea was associated with an eventual requirement for hospitalization while anosmia or ageusia were associated with a decreased risk for need for hospitalization. [15] The same dyspnea and anosmia/ageusia results were found in a smaller cohort of initial outpatients in Seattle, Washington as well. [16] A meta-analysis encompassing 1813 patients revealed that dyspnea was associated with an increased risk for ICU admission (pooled OR 6.55, 95% CI: 4.28-10.0).…”
Section: Discussionsupporting
confidence: 59%
“…The sample sizes ranged from 52 [ 12 ] to 417 366 people [ 13 ]. Most of the studies were hospital-based (34 studies) while three were studies [ 14 16 ] in the community and fourteen had a mixed setting [ 16 28 ]. Studies originate from 21 countries spread on all 5 continents – Europe (n=17), North America (n=13), Asia (n=12), South America (n=5), Africa (n=2) and Australia (n=2).…”
Section: Resultsmentioning
confidence: 99%
“…Scores on the NOS ranged between 6 [ 16 , 29 ] to 9 (maximum 9), with a higher score indicating a high quality. All studies scored 7 or above and were of high quality.…”
Section: Resultsmentioning
confidence: 99%
“…Another study covering the clinical characteristics and factors associated with hospital admission or death in 43,103 adult outpatients described a lower rate of worsening amongst patients who reported being current smokers. The current tobacco use odds ratio was 0.67 [0.47–0.95] for clinical worsening association ( 22 ).…”
Section: Discussionmentioning
confidence: 99%